Contra la subalternidad: resemantización de la imagen intolerable de la mujer en Las Islas Nuevas de María Luisa Bombal. - NOVOA ROMERO, ALEXANDRA (Nomadías)
In the story Las Islas Nuevas by María Luisa Bombal, the woman is represented through a Darstellung (Spivak) that integrates the dreams and desires of the mysterious protagonist. This Darstellung of the oneiric elaborates a sex/gender difference where patriarchal subordination (Segato) is rejected, a practice of decolonization and liberation that brings us closer to a postcolonial ethic (Mignolo). This position becomes even more complex when the story exposes the vision of the man, who tries to elucidate the woman, and observes a monstrous spectacle, a stump on the protagonist's back, an atrophied being, an image created by an intolerable representation (Rancière) that questions the myths held about the image of women.